Blue economy meets international political economy: The emerging picture. (2nd July 2020) - Kedia, Shailly; Gautam, Priyanka
ABSTRACT: Blue economy like green economy tries to bring to forefront the role of economic players, both state and non-state market actors, thus making it important to examine the issue from the lens of international political economy. This article defines blue economy as economic practices that seek to achieve conservation, inclusive development and sustainable use of oceans and seas as commons through poly-centric, multi-level and multi-actor interventions. Blue economy initiatives analysed here include Sustainable Ocean Business Action Platform, World Bank PROBLUE and Sustainable Blue Economy Finance Initiative. The analysed initiatives are not yet designed to appreciate the complexity involving ocean-as-commons. Moreover, the stakeholders mobilised remain concentrated in limited developed countries, mostly from Europe. Even mobilisation of market players remains limited to large companies and boutique firms specific to sustainability. This review argues that blue economy narratives and initiatives need to recognise that ocean systems being complex require poly-centric, multi-level, incremental and learning-based approaches.